Social Perception in Schizophrenia: Evidence of Reduced Prejudiced Attitudes Among People With a Diagnosis of Schizophrenia - Castelli, Luigi; Carraro, Luciana; Valmori, Alessia; Uliana, Chiara; Paparella, Massimiliano (Frontiers in Psychology, 2021)
Only recently research in social psychology has started to systematically investigate intergroup attitudes among members of stigmatized minority groups. In particular, the study of the way people with mental health problems perceive the social groups around them is so far very scarce. In this work, we focused on people with schizophrenia, analyzing their attitudes towards another stigmatized group, namely Black individuals. In Study 1, the attitudes towards White and Black people were assessed in a sample of respondents with a diagnosis of schizophrenia and in a sample of non-clinical individuals. Results showed the presence of less negative attitudes towards the minority outgroup (i.e., Black people) among the clinical sample. In Study 2, we aimed at investigating what members belonging to the majority group (i.e., White non-clinical people) believe about the attitudes towards Black people held by individuals with a diagnosis of schizophrenia. In general, results suggested a general awareness in lay persons that people with a diagnosis of schizophrenia, as compared to people with no history of mental disorders, hold reduced negative attitudes towards Black individuals. Overall, these results may help to enrich our knowledge about social cognition among members of stigmatized groups in general and, more specifically, among individuals with a diagnosis of schizophrenia.